Supply chain strategy - Sillanpää, Ilkka (Management, 2014)
The purpose of this case study research is to present a literature review of supply chain strategy approaches, develop supply chain strategy framework and to validate a framework in empirical case study. Literature review and case study research are the research methods for this research. This study presents the supply chain strategy framework which merges together business environment, corporate strategy, supply chain demand and supply chain strategy. Research argues that all the different concepts that are currently used as supply chain strategy can be condensed into a presented supply chain strategy framework. Developed supply chain strategy framework is a practical tool for business managers. Future research could be multiple case studies in the global environment to develop further the supply chain strategy framework.
Keywords: menagement; nabava; oskrbovalne verige; podjetja; purchasing